Habitat, distribuição e aspectos adaptativos de peixes da microbacia do ribeirão Grande, Estado de São Paulo, Brasil - De Souza Braga, Francisco Manoel [UNESP] (Universidade Estadual de Maringa, 2004)
The ichthyofauna of ribeirão Grande microbasin that runs through one of the few remaining fragments of Atlantic Forest (in Mantiqueira mountain range, Valley of Paraíba) was studied. Fish samples were obtained with an electric fishing powered by a maximum capacity generator of 155 V and 60-Hz alterning current, gill-nets and traps. In three collecting days, during July/2001, October/2001, January/2002 and April/2002, 2865 fishes were sampled. These fishes belonged to 12 families, 23 genera and 37 species. The species were more abundant between the piedmont and the plain of the Valley of Paraíba. The Characidium, Trichomycterus genera and the Imparfinis minutus species presented only one ovary or testis and no swim bladder. The ecological significance of morphological features in stream mountain fishes was used to predict the niche adaptation for those conditions, towards K-strategy.
Habitat, distribution and adaptation features of fishes in ribeirão Grande microbasin, state of São Paulo, Brazil
Keywords: Distribution; Mantiqueira mountain range; Morphology; Ribeirão Grande; Stream fishes; animal experiment; ecology; evolutionary adaptation; fish; morphology; nonhuman; species habitat; Animalia; Characidium; Imparfinis; Pisces; Trichomycterus